الأنساق الثقافية في رواية "غريب" لمحمد جربوعة - عثماني إيمان (My University, 2026)
ABSTRACT This study aims to uncover the cultural patterns embodied in the novel Gharib by Mohamed jer boua. It Seeks to Show how the Social paltern reflects the suffering of the individual and the feelings of alienation and sadness experienced in his Society. The political pattern is represented throu highlighting the oppression marginalization, and loss of rights Suffered by the individual, while the religious pattern reflects the characters adherence to religious pattern reflects the chracters adherence to religious Values and their pursuit of spiritual ideals and commitment ; The novel is characterized by a poetic and symbolic language, as the writer relied on artistic expressions carrying deep meanings that contribute to achieving aesthetic goals. These Stylistic features helped reveal the cultural patterns and highlight the dimensions of the novel. ---------------------- ملخص تهدف منه الدراسة إلى الكشف عن الأنساق الثقافية وتمثلاتها في النص الروائي "غريب" لمحمد جربوعة، حيث سعت الى بيان كيفية تجسيد النسق الاجتماعي من خلال تصوير معاناة الفرد وما يعيشه من اغتراب وحزن في مجتمعه، كما تجلى النسق السياسي في إبراز ما يفتقر إليه الفرد من تهميش وفقدان الحقوق، بينما ظهر النسق الديني في التمسك بالقيم الدينية وسعي الشخصيات في الحصول على الطمأنينة وتجاوز الأزمات، وقد جاءت لغة الرواية شعرية ورمزية اعتمد فيها الكاتب على توظيف معاني عميقة إلى جانب بعض الألفاظ السهلة، فكانت أداة ساهمت في الكشف عن الأنساق الثقافية وإبراز أبعاد الرواية. ------------------------- Résumé Cette étude vise à révéler les structures culturelles et leurs représentations dans le roman «Gharib » (L'étranger) de Mohamed Djerboua. Elle s'efforce de montrer comment la structure sociale se matérialise à travers la description de la souffrance de l'individu, ainsi que l'aliénation et la tristesse qu'il vit au sein de sa société. De même, la structure politique transparaît en mettant en évidence la marginalisation et la perte des droits dont souffre l'individu. Enfin, la structure religieuse se manifeste à travers l'attachement aux valeurs spirituelles et la quête des personnages pour atteindre la sérénité et surmonter les crises, Le langage du roman est poétique et symbolique, l'auteur s'appuyant sur l'usage de significations profondes associées à des termes simples. Ce style a constitué un outil majeur ayant contribué à dévoiler les structures culturelles et à mettre en valeur les dimensions de l'œuvre
Keywords: Cultural patterns; social pattern; political pattern; religious pattern; historical pattern; alienation.; الأنساق الثقافية، النسق الاجتماعي، النسق السياسي، النسق الديني النسق التاريخي، الاغتراب; Structures culturelles; structure sociale; structure politique; structure religieuse; modèle historique; aliénation